2002
DOI: 10.1038/sj.bjc.6600356
|View full text |Cite
|
Sign up to set email alerts
|

Implication of mitochondria-derived ROS and cardiolipin peroxidation in N-(4-hydroxyphenyl)retinamide-induced apoptosis

Abstract: {We have studied the effect of N-(4-hydroxyphenyl)retinamide on either malignant human leukaemia cells or normal cells and investigated its mechanism of action. We demonstrate that 4HPR induces reactive oxygen species increase on mitochondria at a target between mitochondrial respiratory chain complex I and II. Such oxidative stress causes cardiolipin peroxidation which in turn allows cytochrome c release to cytosol, caspase-3 activation and therefore apoptotic consumption. Moreover, this apoptotic pathway see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 19 publications
6
57
1
Order By: Relevance
“…We have reported previously that the ROS-dependent phosphorylation of p38 MAPK is required for fenretinideinduced cell death in ESFT (Myatt et al, 2005), consistent with the hypothesis that induction of ROS is responsible for the selectivity of fenretinide for malignant cells (Asumendi et al, 2002;O'Donnell et al, 2002). The induction of ROS by fenretinide within an ESFT cell line, but not across ESFT cell lines, correlates with the degree of cell death observed following exposure to fenretinide.…”
Section: Discussionsupporting
confidence: 54%
“…We have reported previously that the ROS-dependent phosphorylation of p38 MAPK is required for fenretinideinduced cell death in ESFT (Myatt et al, 2005), consistent with the hypothesis that induction of ROS is responsible for the selectivity of fenretinide for malignant cells (Asumendi et al, 2002;O'Donnell et al, 2002). The induction of ROS by fenretinide within an ESFT cell line, but not across ESFT cell lines, correlates with the degree of cell death observed following exposure to fenretinide.…”
Section: Discussionsupporting
confidence: 54%
“…JNK inhibitor suppresses cytochrome c release from mitochondria JNK has been shown to be required for cytochrome c release from mitochondria in stress-induced apoptosis (Tournier et al, 2000) and 4HPR has been shown to induce cytochrome c release from mitochondria in various cell types (Suzuki et al, 1999;Asumendi et al, 2002;Boya et al, 2003). To delineate the mechanism of JNK function in 4HPR-induced apoptosis in 22B cells, we examined the effect of SP600125 on mitochondrial events induced by 4HPR.…”
Section: Pharmacological Inhibitor Of Jnk Suppresses 4hpr-induced Celmentioning
confidence: 99%
“…Increased generation of reactive oxygen species (ROS) (Delia et al, 1997;Suzuki et al, 1999;Hail and Lotan, 2001), increased ceramide production (Maurer et al, 1999), induction of mitochondrial permeability transition (MPT) (Suzuki et al, 1999;Hail and Lotan, 2000;Poot et al, 2002;Boya et al, 2003), cytochrome c release (Suzuki et al, 1999;Asumendi et al, 2002;Boya et al, 2003), increased GADD153 (Kim et al, 2002;Lovat et al, 2002), and activation of 12-lipoxygenase (Lovat et al, 2002) or activation of c-Jun N-terminal kinase (JNK) (Chen et al, 1999;Shimada et al, 2002;Osone et al, 2004) have been implicated in 4HPR-mediated apoptosis in various cancer cells. In addition, retinoid receptors may contribute to 4HPR-induced apoptosis in some cells (Sun et al, 1999;Lovat et al, 2000;Ulukaya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…4A show that 300 nmol/L CDDO-Me selectively depleted GSXm by 69% (P < 0.003) in KBM5 cells, and a similar effect was seen in KBM5-STI cells (65%; P < 0.02) after 3-h treatment without any marked effect in whole-cell GSX, supporting the notion that the triterpenoid structure of CDDO-Me may mediate perturbations in GSXm flux. Cardiolipin is the most abundant phospholipid in the mitochondrial membrane and has been shown to modulate the initiation of the intrinsic apoptotic pathway (29,30). Because GSXm is critical for the maintenance of cardiolipin (31 -33), we examined the levels of cardiolipin in cells treated with CDDO-Me by staining with the cardiolipin-selective fluorochrome nonyl acridine orange (NAO).…”
Section: Cddo-me Induces a Rapid And Selective Depletion Of Mitochondmentioning
confidence: 99%